Communist International in 1920-s: British direction of activity - A. Y. Prokopov (Vestnik MGIMO-Universiteta)
In this article the main attention of the author is devoted to the problem of the decisive influence of the Communist International and its tactic “the united workers front” (1921—1928) on the policy of the Communist Party of Great Britain (CPGB) towards the Labour Party, the British Congress of Trade-Unions and the first Labour Government (1924). The author also examines the influence of Comintern on the activity of the CPGB before parliament elections of 1922, 1923, 1924 and during the General Strike of 1926.